Climate Action Plans, an Essential Planning Tool for Cities - Horn, Christian (project baikal, 2019)
Climate change is happening on a faster pace than ever recorded before. It has become visible in multiple wildfires on nearly all continents, heat waves, melting glacier, thawing of permafrost, water shortage, the reduction of the biodiversity and other occurrences. The Paris agreement, based on the negotiations of the 21st Conference of the Parties in Paris (COP21) in December 2015, focus to contain global warming well below 2°C compared to pre-industrial levels by 2100, and strives to limit the increase to +1.5°C. To implement the objectives of the Paris agreement on their territories, many European cities developed their municipal climate action plans with the objective of becoming carbon neutral by 2050. To achieve this objective, it is crucial to involve all stakeholders: public and private entities, associations and citizens, as about 80% (in the case of Paris) of the objective are depending of their implication and changes in behaviour.